دراسة غزارة الإشباع وفق HCM2010 ومقارنتها مع القياس الحقلي على التقاطعات المنظمة بإشارات ضوئية (حالة درسية: مدينة طرطوس ) - داؤد, شفيق; رستم, أكرم; ابراهيم, محمد (Latakia University Journal -Engineering Sciences Series, 2018)
يشكل تقييم سعة التقاطعات المنظمة بإشارات ضوئية أحد أهم الأسس المستخدمة في تخطيط وتصميم وتشغيل وإدارة شبكة الشوارع في المدن، ويعتمد حساب السعة على تقدير قيمة غزارة الإشباع على التقاطعات المنظمة بإشارات ضوئية. يتم استخدام طريقة دليل سعة الطرق السريعة الأمريكي (HCM2010) في تقدير وتحليل غزارة الإشباع، وهذه الطريقة مستخدمة بشكل واسع في دول العالم ومنها سوريا، ولكن هذا الدليل يعبر عن الظروف المحلية في الولايات المتحدة الأمريكية، ولذلك قد لا يكون مناسباً لاستخدامه في ظروفنا المحلية. يتناول هذا البحث تقدير غزارة الإشباع حقلياً بالاعتماد على الفواصل بين العربات ضمن الأرتال، ومقارنة النتائج الحقلية لغزارة الإشباع مع القيم الناتجة عن استخدام طريقة HCM. تم اجراء الدراسة على ثلاث تقاطعات في مدينة طرطوس، واستند التحليل على تجميع البيانات باستخدام الفيديو. أكدت النتائج النهائية أن هناك اختلاف بين القيمة الحقلية لغزارة الإشباع والقيمة الحسابية، مما يؤكد عدم امكانية استخدامها لظروفنا المحلية. The evaluation of the capacity of signalized intersections is one of the most important parameter used in the planning, design, operation and management of urban street networks. The calculation of capacity depends on the estimation of the saturation flow of the signalized intersections. The highway Capacity Manual (HCM 2010) is used to estimate and analyze the saturation flow. This method is widely used in many countries around the world, including Syria. It reflects the local conditions in the United States of America; therefore it may not be suitable for use in our local conditions. This study includes estimation of the field saturation flow depending on the headways between the vehicles in the queues, and comparing the field results of the saturation flow with the values resulting from using the HCM. The study was conducted on three intersections in the Tartous city. The analysis was based on data collection using video. The final results confirmed that there is a clear difference between the field measurement of the saturation flow and computation value, Which confirms that it cannot be used for our local conditions.